Estimating Carbon Dynamics in an Intact Lowland Mixed Dipterocarp Forest Using a Forest Carbon Model - Jongyeol Lee (Forests, 2017)
Intact dipterocarp forests in Asia act as crucial carbon (C) reservoirs, and it is therefore important to investigate the C dynamics in these forests. We estimated C dynamics, together with net ecosystem production (NEP), in an intact tropical dipterocarp forest of Brunei Darussalam. Fifty-four simulation units (plots; 20 m × 20 m) were established and initial C stocks were determined via direct field measurement. The C dynamics were annually simulated with a regression model and the Forest Biomass and Dead organic matter Carbon (FBDC) model. The initial C stock (Mg C·ha−1) of biomass, litter, dead wood and mineral soil were 213.1 ± 104.8, 2.0 ± 0.8, 31.3 ± 38.8, and 80.7 ± 15.5, respectively. Their annual changes (Mg C·ha−1·year−1) were 3.2 ± 1.1, 0.2 ± 0.2, −3.7 ± 6.1, and −0.3 ± 1.1, respectively. NEP was −0.6 ± 6.1 Mg C·ha−1·year−1, showing large heterogeneity among the plots. The initial C stocks of biomass and dead wood, biomass turnover rates and dead wood decay rates were elucidated as dominant factors determining NEP in a sensitivity analysis. Accordingly, investigation on those input data can constrain an uncertainty in determining NEP in the intact tropical forests.